2018
DOI: 10.1158/0008-5472.can-17-2388
|View full text |Cite
|
Sign up to set email alerts
|

Selective mTORC2 Inhibitor Therapeutically Blocks Breast Cancer Cell Growth and Survival

Abstract: Small-molecule inhibitors of the mTORC2 kinase (torkinibs) have shown efficacy in early clinical trials. However, the torkinibs under study also inhibit the other mTOR-containing complex mTORC1. While mTORC1/mTORC2 combined inhibition may be beneficial in cancer cells, recent reports describe compensatory cell survival upon mTORC1 inhibition due to loss of negative feedback on PI3K, increased autophagy, and increased macropinocytosis. Genetic models suggest that selective mTORC2 inhibition would be effective i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 61 publications
0
51
0
Order By: Relevance
“…[10][11][12][13] Indeed, the development of glucose intolerance and insulin resistance in transplant patients receiving rapamycin may be mediated by mTORC2 inhibition. 14,15 However, although selective mTORC2 targeting has been shown recently to block tumor growth in mice, 16,17 we are not aware of any reports of selective mTORC2 targeting in graft donors or recipients. 14,15 However, although selective mTORC2 targeting has been shown recently to block tumor growth in mice, 16,17 we are not aware of any reports of selective mTORC2 targeting in graft donors or recipients.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…[10][11][12][13] Indeed, the development of glucose intolerance and insulin resistance in transplant patients receiving rapamycin may be mediated by mTORC2 inhibition. 14,15 However, although selective mTORC2 targeting has been shown recently to block tumor growth in mice, 16,17 we are not aware of any reports of selective mTORC2 targeting in graft donors or recipients. 14,15 However, although selective mTORC2 targeting has been shown recently to block tumor growth in mice, 16,17 we are not aware of any reports of selective mTORC2 targeting in graft donors or recipients.…”
mentioning
confidence: 98%
“…11 In mice, dual inhibition of mTORC1 and mTORC2 using novel adenosine triphosphase (ATP) competitive inhibitors is less effective in prolonging heart allograft survival than is immune suppression with rapamycin alone. 14,15 However, although selective mTORC2 targeting has been shown recently to block tumor growth in mice, 16,17 we are not aware of any reports of selective mTORC2 targeting in graft donors or recipients.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that selective or targeted mTORC2 inhibition causes reduced cell proliferation, tumor size, and angiogenesis in several types of cancers including colon cancer, breast cancer and multiple myeloma [49][50][51][52][53]. Differential effects of dose-interval schedules of rapamycin (or rapalogs) on colon cancer have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al (2018) developed a nanoparticle-based RNAi therapeutic that could effectively silence the mTORC2 cofactor RICTOR. By intratumoral or intravenous delivery, nanomedicine in combination with lapatinib impaired the survival of HER2-amplified breast cancer cells (Werfel et al 2018).…”
Section: Breast Cancermentioning
confidence: 99%